From Religious Identity to Cultural Citizenship: Identity Transformation and Civil Rights Negotiation among MLKI Banyumas - Abdul Qodir Abdillah; Roibin; Lutfi Mustofa (Refleksi: Jurnal Kajian Agama dan Filsafat, 2026)
This research examines how the community of religious adherents who are members of the Supreme Council of Belief in the One Almighty God of Indonesia (MLKI) in Banyumas transforms their religious identity into a cultural identity as a strategy to negotiate recognition and obtain civil rights. This article puts forward a conceptual argument that differs from existing legal-administrative studies: rather than viewing recognition solely as a matter of state regulation, this article frames identity transformation as a deliberate practice of cultural citizenship (cultural citizenship). The analysis is built primarily on Amartya Sen's theory of identity specifically the distinction between singular identity, plural identity, and the "illusion of identity" and is strengthened by Erving Goffman's concept of stigma, Axel Honneth and Charles Taylor's theory of recognition, and Stuart Hall's notion of cultural identity. Using a qualitative socio-anthropological approach through observation, in-depth interviews, and documentation, this study found that MLKI Banyumas reduces stigma and discrimination by highlighting cultural dimensions through activities such as visiting and participating in the Religious Harmony Forum (FKUB), thus transforming marginalized religious identities into recognized cultural identities without abandoning their beliefs. The novelty of this article lies in theorizing cultural identity as a form of negotiated citizenship strategy, through which marginalized faith communities gain social legitimacy while maintaining their spiritual beliefs.